Physico-chemical characteristics of green and roasted coffee beans (Coffea arabica L.) of IAPAR (Coffee Science - ISSN 1984-3909, 2011)
Environmental conditions exert strong influence on the quality of the coffee beverage in such a way that selection of new cultivars requires information about the composition and characteristics of coffee beans produced in different places. The objective of the present study was to evaluate the physico-chemical components of the green and roasted coffee beans (Coffea arabica L.) of the cultivars: IPR 98, IPR 99, IPR 100, IPR 101, IPR 102, IPR 103, IPR 104, IPR 105, IPR 106, IPR 107, IPR 108, IAPAR 59, Catuaí, Bourbon, Tupi and Icatu, harvested in experimental fields in Paranavaí and Itaguajé - PR, in the 2007-2008 harvest. In the processed coffee we determined the apparent density. Total proteins and sugars, reducing sugars, sucrose, hidrosoluble tannin, chlorogenic acids and caffeine were determined in the green coffee beans. The apparent density, expansion of volume and chromatic components had been determined in the roasted coffee beans. Significant differences were observed in the Physico-chemical composition and characteristics of the coffees beverage of each location. Through PCA we noted that Itaguajé and Paranavaí cultivars were differentiated according to the grain size and density, sugars, proteins, lipids, pH, titratable acidity and the color components. In the same location cultivars differ mainly in function of the concentration of chlorogenic acids. It was also noted that cultivars, grouped through HCA (Hierarchical Clustering Analysis), exhibited similar characteristics among themselves, demonstrating environmental effects on genetic expression in the cultivars.